The Atomic Bazaar : The Rise of the Nuclear Poor - Langewiesche, William (London Allen Lane, 2007)
Presents an investigation of the drift of nuclear weapons technology from the hands of the rich into the hands of the poor. This book takes us to the smuggling back routes in Turkey and to the 'nuclear cities' in Russia, which housed nearly a million people for decades. It describes a reality that the West must face.
Include Map and Acronyms
Keywords: Nuclear weapons. -- Nuclear weapons -- Pakistan. -- World politics